Development of a Language Attitude Instrument and its Application to Survey Islamic High School Students' Language Attitudes towards English - Kholid Jarnudi; Sholeh Hidayat; Syafrizal Syafrizal; John Fahamzah; A. Amrudin (Jurnal Pendidikan Indonesia Gemilang, 2024)
This research aimed to provide an overview of how to develop a language attitude instrument to measure students' attitudes towards English, what aspects must be included in the language attitude instrument, and how students' language attitudes towards English. This research is descriptive research that used a quantitative approach. The research was conducted at a state islamic senior high school in Serang City, Indonesia with a total sample of 160 students spread across science, social, and religious departments. The development of language attitude instruments has to pay attention to the components of language attitudes, which are cognitive, affective, and conative components. Based on the data analysis of the results of the validity and reliability test of the instrument, it can be concluded that all items of the language attitude instrument are declared valid and reliable. Furthermore, referring to the description of the language attitude data of students in Serang City, Indonesia, it shows that on average students tend to have positive language attitudes towards English.